"We Prefer Local but Consume Imported": Results from a Qualitative Study of Dairy Consumers in Senegal. Issue 2 (15th March 2023) - Boimah, Mavis; Weible, Daniela
Abstract: Senegal's dairy sector is faced with relatively cheap imports mainly from Europe. Besides price, other factors such as product characteristics may possibly drive consumer decisions. Therefore, this study is carried out using focus group discussions to gain an understanding of Senegalese consumers' perceptions and preferences toward local, domestic, and imported dairy products. Results show that consumers strongly prefer local dairy products because they perceive them as natural and healthy, nevertheless, they are motivated to purchase domestically processed and imported products based on attributes such as availability, accessibility, diversity, longer shelf life in addition to lower prices. Also, in spite of the strong preference for local products, consumers are in doubt regarding their safety. The findings point to the need for developing the entire dairy value chain of Senegal, however, policies formulated to achieve this course should not ignore the negative environmental effects of dairy intensification.